Comparison of Multilayer Transparent Wood and Single Layer Transparent Wood With the Same Thickness - Wu, Yan; Wang, Yajing; Yang, Feng (Frontiers in Materials, 2021)
In this paper, poplar was used as raw material, sodium chlorite was used to delignify it in acidic environment, and then epoxy resin was vacuum impregnated in the delignified wood template to prepare transparent wood. Moreover, in order to imitate the lamination method of plywood, the multilayer transparent wood was prepared by means of staggered vertical lamination, which greatly improved the thickness of transparent wood. The purpose of this paper is to study the physical and chemical properties of multilayer transparent wood, and to explore the application potential of multilayer transparent wood as a new material by comparing with single layer transparent wood with the same thickness. Scanning electron microscopy (SEM) measurements, Fourier transform attenuated total reflection infrared spectroscopy (ATR-FTIR) characterization, weight gain measurements, UV transmittance measurements, color difference measurements, water contact angle measurements and mechanical properties measurements were used to study. The results show that the transmittance and mechanical properties of multilayer transparent wood are better than that of single layer transparent wood with the same thickness. The specific performance is that the same thickness of transparent wood due to its different fiber direction would produce a certain difference in light transmittance. The transmittance of transparent wood with different thickness decreased with the increase of thickness. The light transmittance of multilayer transparent wood is higher than that of single layer transparent wood with the same thickness. Moreover, compared with the single layer transparent wood with the same thickness, the lightness of the multilayer transparent wood decreased, and tended to be yellow and red. The tensile strength of transparent wood decreased due to the removal of lignin in the preparation process. However, the tensile strength of multilayer transparent wood is much higher than that of single layer transparent wood, which can improve this defect to some extent. Multilayer transparent wood can solve the problem of small thickness of single layer transparent wood to a certain extent. It is a kind of natural transparent material with large thickness, good transmittance and excellent mechanical properties, and has a good development prospect.